1989
DOI: 10.1002/jcc.540100606
|View full text |Cite
|
Sign up to set email alerts
|

Chlorosilanes: Development and application of MM2 force field parameters

Abstract: The geometries, relative conformational energies, and dipole moments of mono and polychlorosilanes have been calculated using ab initio molecular orbital (MO) theory. Calculations at the HF/3-21G(*) level, with the exception of dipole moments, give reasonable agreement with experimental data. A new MM2 force field for chlorosilanes, which includes terms for bond length shortening and bond angle compression due to the attachment of electronegative C1 atoms, has been developed on the basis of experimental and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 99 publications
1
11
0
Order By: Relevance
“…Similarly, there is a slight quantitative discrepancy between our values for 2 (Δ E MP2, Δ E BestEst. = +0.40 kcal mol −1 and Δ E BestEst.o = +0.34 kcal mol −1 ) versus Δ E from MM2 calculations (+0.635 kcal mol −1 ) 6.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, there is a slight quantitative discrepancy between our values for 2 (Δ E MP2, Δ E BestEst. = +0.40 kcal mol −1 and Δ E BestEst.o = +0.34 kcal mol −1 ) versus Δ E from MM2 calculations (+0.635 kcal mol −1 ) 6.…”
Section: Resultsmentioning
confidence: 97%
“…Conformational analysis of silanes was prevalent in the 1970–1990s in order to develop and optimize molecular mechanics force fields for silicon containing compounds. These force fields were built to gain a better understanding of the stereochemical effects that silicon imparts on the molecule 3–8. The conformational analysis of the chair, boat, twist boat, and sofa conformations of silacyclohexane has been examined by quantum mechanical methods to determine interconversion pathways, structural parameters, and relative energies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the course of these studies, we observed unusual outcomes in various geometric features, which arise probably due to strong polarization of chlorosilane derivatives. Furthermore, we found that most of the ab initio calculations including HF/6-31G* substantially overestimate experimental dipole moments 4a. These abnormal results are somewhat surprising because a HF/6-31G* calculation is generally accepted to furnish reasonably good values of dipole moments in a variety of molecules including some silicon containing compounds .…”
Section: Introductionmentioning
confidence: 78%
“…Their electronic natures have not been explored thoroughly yet, even though they have been applied widely in synthetic organic chemistry . We were involved in the development of molecular mechanics (MM2) parameters for chlorosilanes some years ago and focused mainly on molecular structures and conformational energies to identify a stable conformer among various diastereomers in alkyl substituted chlorosilacyclohexane derivatives 4a. During the course of these studies, we observed unusual outcomes in various geometric features, which arise probably due to strong polarization of chlorosilane derivatives.…”
Section: Introductionmentioning
confidence: 99%